RELIGIOUS FAITH: EXISTENTIAL-ANTHROPOLOGICAL MEANINGS - O. I. Predko (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The aim of this article is to analyse the essential features of religious faith as an existential-personalistic model of the formation of a person, his worldview orientations and activities. This requires a consistent solution of the following tasks: a) to focus on different approaches to understanding the phenomenon of "religious faith" (as a problem of principled openness, incompleteness of a person; as the problem of "I-Other" relations; as a problem of synthesis of the human and the divine, etc.); b) to reveal the spiritual potential of religious faith, its capabilities in boundary situations. Theoretical basis. The author thinks that the interpretation of religious faith as confidence in the invisible is unsatisfactory, one-sided and superficial. Religious faith is the existential, due to which a person overcomes the contradictions between finiteness and infinity. It is the construct of the human spirit, which makes its way into the transcendental realm. In this context, religious faith is a kind of criterion for the "growth" of the "human" in human, the criterion of his spirituality and humanity. Religious faith, being an integral part of human existence, gives it irrational dimensions, makes the possibility of impossible. The existential potential of religious faith serves as the "fulcrum" of a person, thanks to which he self-actualizes, self-fulfills and forms a certain worldview model. Originality. The author has proved that religious faith, which is the projective model of a person, turns out to be one of the possible ways to solve its existential problems, as it concerns not only the nature of the essential characteristics, the properties of the Divine itself but also the ultimate foundations of person in all the uniqueness and specificity of his being. Conclusions. Religious faith, acting as a factor in human activity, builds his value-worldview model of the world. Faith deals with the "ultimate" problems of human existence since it is of exceptional importance in solving life-meaning issues of human existence. The existential experience of the believer acquires the status of an event that opens up a field of new possibilities, a new spiritual experience. The accumulative effect of such experience forms the spiritual and value priorities of human existence, sets certain coordinates of his vital activity, due to which he self-determines, being in dialogue with the Absolute. Religious faith, unfolding as a permanent process of "search and finding" opens the "code" of transcendence, a new level of relations of the Human and Divine.